Eosinophilic granulomatosis with polyangiitis – Advances in pathogenesis, diagnosis, and treatment - Fijolek, Justyna; Radzikowska, Elzbieta (Frontiers in Medicine, 2023)
Eosinophilic granulomatosis with polyangiitis (EGPA) is a rare disease characterized by eosinophil-rich granulomatous inflammation and necrotizing vasculitis, predominantly affecting small-to-medium-sized vessels. It is categorized as a primary antineutrophil cytoplasmic antibody (ANCA)-associated vasculitides (AAVs) and hypereosinophilic syndrome (HES); therefore, both vessel inflammation and eosinophilic infiltration are suggested to cause organ damage. This dual nature of the disease causes variable clinical presentation. As a result, careful differentiation from mimicking conditions is needed, especially from HES, given the overlapping clinical, radiologic, and histologic features, and biomarker profile. EGPA also remains a diagnostic challenge, in part because of asthma, which may predominate for years, and often requires chronic corticosteroids (CS), which can mask other disease features. The pathogenesis is still not fully understood; however, the interaction between eosinophils and lymphocytes B and T seems to play an important role. Furthermore, the role of ANCA is not clear, and only up to 40% of patients are ANCA-positive. Moreover, two ANCA-dependent clinically and genetically distinct subgroups have been identified. However, a gold standard test for establishing a diagnosis is not available. In practice, the disease is mainly diagnosed based on the clinical symptoms and results of noninvasive tests. The unmet needs include uniform diagnostic criteria and biomarkers to help distinguish EGPA from HESs. Despite its rarity, notable progress has been made in understanding the disease and in its management. A better understanding of the pathophysiology has provided new insights into the pathogenesis and therapeutic targets, which are reflected in novel biological agents. However, there remains an ongoing reliance on corticosteroid therapy. Therefore, there is a significant need for more effective and better-tolerated steroid-sparing treatment schemes.